Influence of four organic amendments on the development of Pitahaya (Hylocereus Spp.) Var plants. American Beauty in the Pataz District, La Libertad Region-Peru - Huamanchay Rodríguez, Willian Marcelino (2024)
The present thesis study was carried out in the Calquiche Sector of the Chagual Annex, in the Pataz District, Pataz province, La Libertad Region, during the period between December 2021 and October 2022. The main objectives were to evaluate the impact of organic amendments in the American beauty variety of pitahaya on various growth parameters. Measurements were made of the number of stem buds per plant, stem length, total plant height, and root length. To carry out this study, a sample of 75 plants was used, applying different organic amendments: chicken manure, sheep manure, worm humus, island guano and a control group without amendments (control). The experimental design was a completely randomized block (DBCA), with 3 repetitions and 5 treatments, each with 15 units for experimentation. Regarding the statistical analysis, an analysis of variance (ANOVA) was applied with a probability F of 0.05 and 0.01. In addition, Duncan and Tukey tests were run with a confidence level of 95%. The results revealed that organic amendments, especially chicken manure and sheep manure, promoted significant plant development. These treatments demonstrated an increase of 1.67 and 1.53 in the number of stem shoots per plant respectively, as well as a greater total plant height, reaching 95.2 cm and 87.67 cm, and a root length of 30.98 cm and